Dinâmica da inversão do saco vitelino em preás Galea spixii Wagler, 1831 - Vale, André Menezes do (2011)
The inversion period of the yolk sac as the dynamic which results from this process was studied in 30 female of prea on days 6, 10, 11 to 15, 20, 25, and 30 of gestation. Six groups of animals (one male for five females) were formed and kept in boxes of 5m2. Vaginal cytology was performed daily for detection of copulation. Pregnant females were separated of the other individuals of the group. They were euthanized using a specific anesthetic protocol for collection of the gestational sacs. Then, the material was processed for histology, immunohistochemistry, scanning electron microscopy, and transmission electron microscopy. At days 11 to 13 of gestation was observed the development of the parietal and visceral endoderm delimiting the yolk sac cavity. The parietal endoderm was coating the surface of the fetal side of the chorioallantoic placenta and surrounding the space bounded by the capsular decidua. These endoderm layers showed a prismatic shape and were separated of the trophoblast by a developed Reichert s membrane. The visceral endoderm contained vitelline vessels and villi in some areas. On the 13th day it was possible to establish as a basic condition before the inversion of teh yolk sac, the permanence of at least one of the three elements that characterized the bilaminar omphalopleure. On the 14th day of gestation the complete inversion of the yolk sac, which was characterized by the degeneration of both parietal endoderm and mural trophoblast, coupled with the gradual disappearance of the Reichert s membrane was observed. As a consequence of this, the visceral endoderm constitutes the interface with the uterine epithelium. After the inversion of the yolk sac, the parietal endoderm remained intact was the one which rested on the surface of the chorioallantoic placenta, which showed high columnar cells, characteristic of the pseudostratified epithelium. The visceral endoderm showed numerous apical villi mainly in regions close to the chorioallantoic placenta. The intense vascularization was confirmed by the immunohistochemistry reaction for vimentin associated with the scanning electron microscopy. During the continuous development of the embryo and chorioallantoic placenta it was also observed the development of an important area of apposition of both visceral and parietal endoderm whose proliferative capacity of these cells was demonstrated by immunohistochemistry using PCNA antibody. Therefore, we concluded the inversion of the yolk sac represents an anatomical arrangement in favor of embryonic development as well as an evolutionary characteristic in this rodent specie.